Faktor Determinan Perilaku Pedagang dalam Penggunaan Bahan Tambahan Pangan Berbahaya pada Jajanan Sekolah Dasar di Wilayah Kecamatan Laweyan Surakarta - Ghefira Nazma Arroyan; Windi Wulandari (Jurnal Pengabdian Ilmu Kesehatan, 2026)
School canteen foods in elementary school settings carry a significant risk of containing hazardous chemical substances including methane yellow, rhodamine B, formalin, and borax which pose serious health threats to young children. This research aimed to examine the determinant factors associated with vendor behavior regarding the use of prohibited food additives in snacks sold around elementary schools in Laweyan District, Surakarta. An observational quantitative method with a cross-sectional design was employed. The study involved 80 street vendors recruited through total sampling, alongside laboratory testing of 140 food samples. Data collection was carried out using structured questionnaires, field observation, and documentation review. Analysis was conducted at both univariate and bivariate levels. Findings revealed that the majority of vendors fell within the 30–49 year age range (55.0%), attained junior high school as their highest education level (36.3%), and had been operating their business for over five years (67.5%). Most vendors demonstrated unfavorable attitudes (58.8%) and poor behavioral practices (53.8%) concerning unpermitted food additives. Statistical testing indicated no significant association between vendor behavior and the variables of age (p=0.637), educational background (p=0.340), duration of trade (p=1.000), or attitude (p=0.422). These outcomes suggest that the tendency to use hazardous food additives is not meaningfully driven by demographic or individual characteristics alone, but rather appears to stem from economic pressures, insufficient specific awareness of food safety, and inadequate regulatory enforcement. The study underscores the necessity for targeted, behavior-based educational interventions as a means of fostering safer food preparation practices and safeguarding the health of the school-age population.